Building A Moral Generation: Reflections On Islamic Values In Modern Life - St. Rahmah; Arifannisa Arifannisa (PT. Anagata Sembagi Education, 2025)
This study aims to identify relevant Islamic values in developing noble character in the younger generation, describe their application in modern life, and analyze the challenges and opportunities faced. The research method used is qualitative with a descriptive approach, through in-depth interviews, participant observation, and document analysis. The results show that the values of honesty (shidq), responsibility (amanah), politeness (adab), and tolerance (tasamuh) are the main foundations for character formation of the younger generation. The implementation of these values can be done through habituation in the family, educational, and community environments, as well as through the positive use of digital media. Key challenges include the influence of popular culture, negative behavior on social media, and the lack of role models. However, significant opportunities arise through the hijrah trend, the proliferation of Islamic content, and the use of technology for creative and adaptive moral development